Conventional angiography findings in hemodynamically unstable patients with acute abdominal hemorrhage and a negative CT bleeding study - O’Brien, Amy C. (CVIR Endovasc, 2020)
BACKGROUND: CT bleeding study (CTA) is regularly requested in acute abdominal haemorrhage (AAH) with haemodynamic instability by clinical teams and interventional radiologists because CTA can; detect arterial bleeding at low rates of hemorrhage, accurately localize the bleeding point and characterize the etiology. How best to manage an unstable patient who has an AAH with a haematoma and no acute vascular findings on CTA represents a difficult clinical scenario for treating physicians and Interventional Radiologists. PURPOSE: To review the conventional angiography (CA) findings and clinical outcome of hemodynamically unstable patients with AAH who had a preceding negative CTA. MATERIALS AND METHODS: All patients who were hemodynamically unstable and underwent CTA and CA for acute arterial abdominal hemorrhage at our institution between 01/01/2010 and 31/12/2017 were identified. Patients with obstetric, penetrating trauma, abdominal aortic or venous sources of hemorrhage were excluded. Patients who had a negative CTA before CA were included. Patient medical records were reviewed for clinical outcome. RESULTS: In the study period 160 hemodynamically unstable patients underwent 178 CA procedures. 155 CA procedures were preceded by CTA. 141 CTAs demonstrated active bleeding or an abnormal artery. 14 CTAs in 13 patients demonstrated hematoma but no acute bleeding (mean age = 56-years; M:F, 12:1). Eight of the 14 CA studies demonstrated: active bleeding (n = 4), pseudoaneurysm (n = 1) or a truncated artery (n = 3). Cases of renal hemorrhage demonstrated a significantly higher proportion of false negative CTA studies (36%). Selective (n = 8) or empiric (n = 4) embolization was performed in twelve cases. All patients stopped bleeding and there were no mortalities. CONCLUSION: In a cohort of hemodynamically unstable patients, 57% (8/14) of cases with no acute vascular findings on CTA demonstrated a source of hemorrhage on CA. The false negative rate of CTA was significantly higher for renal tract hemorrhage compared to other sites of bleeding.